Analysis of International Literature on Bilingual and Multilingual Turkish Children by Bibliometric Analysis Technique - Bekir İnce (Sakarya University Journal of Education)
The aim of this study is to examine the academic publications in the international literature on bilingual and multilingual Turkish children using the bibliometric analysis technique. To this end, the data of 569 studies obtained by querying from the Web of Science database were used for the research. Co-occurrence analysis was used to examine the most frequently used keywords in the analysis, and citation analysis was used in the analysis of authors, articles, journals, institutions and countries and the analyzes were performed with the Vosviewer software. According to the results of the analysis, except for the keywords directly related to the search query such as “Bilingualism”, “Turkish”, “Multilingualism”, “Bilingual”, “Turkey”, keywords such as German, English, Dutch and migration were observed to be frequently used. Moreover, the most cited authors were found to be Paul P.M. Leseman, Elma Blom, and Vasiliki Chondrogianni, while the most cited articles were seen as published in journals related to the field of applied psycholinguistics. In addition, Applied Psycholinguistics, Applied Linguistics and Journal of Pragmatics were noted as the journals with the highest average number of citations per publication. While it was observed that the institutions with the best publication citation averages were Boston University, Istanbul University and Utrecht University, the countries with the best publication citation averages were England, the Netherlands and Denmark